New species and records of freshwater Chaetonotus (Gastrotricha: Chaetonotidae) from Sweden - Kånneby, Tobias (Zootaxa, 2013)
Chaetonotus is the most speciose genus of the family Chaetonotidae within Gastrotricha, a small phylum of aquatic acoelomate invertebrates. The freshwater gastrotrich fauna of Sweden has been studied during the last five years and so far 44 species have been reported in the literature from the country. This study describes the new species, Chaetonotus (Primochaetus) veronicae n. sp., and reports 9 species new to the Swedish fauna raising the known number of freshwater species from the country to 54. Some records stand out from a biogeographic point of view: Chaetonotus (Primochaetus) soberanus is reported for the first time from Europe and Chaetonotus (Chaetonotus) arethusae, Chaetonotus (Chaetonotus) naiadis and Chaetonotus (Hystricochaetonotus) euhystrix are reported for the first time outside the countries from which they were originally described.